2000
DOI: 10.1136/qhc.9.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Complications of diabetes: screening for retinopathy and management of foot ulcers

Abstract: This paper is based on EVective Health Care, volume 5, number 4, 1 which is based on two systematic reviews undertaken to inform national clinical practice guidelines for type 2 diabetes.2 3 The first part of the article looks at screening for diabetic retinopathy and the second at the prevention and treatment of diabetic foot ulcers.Two of the most common complications of diabetes are visual problems caused by retinopathy, and problems with the feet, particularly persistent ulcers. These result from microvasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The intervention resulted in statistically significant improvement for the indicators pertaining to foot examination and eye examination. Foot care reduces amputation rates and early treatment of retinopathy prevents blindness [13 ]. The positive effect on foot examination confirms the results of a British trial in general practice evaluating the implementation of an integrated diabetic footcare model with use of educational practice visits [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention resulted in statistically significant improvement for the indicators pertaining to foot examination and eye examination. Foot care reduces amputation rates and early treatment of retinopathy prevents blindness [13 ]. The positive effect on foot examination confirms the results of a British trial in general practice evaluating the implementation of an integrated diabetic footcare model with use of educational practice visits [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in the type 2 diabetes population, lower-limb ulceration, recurrent ulceration, and amputation remain frequent events with incidence rates as high as 3.0%, 25%, and 0.8% per year, respectively [59]. A recent estimate of the lifetime prevalence of foot ulceration is 15% [6]. It has been demonstrated that a program of intensive weekly multidisciplinary clinic visits with chiropody, education, and use of proper hygiene, hosiery, and protective shoes in high-risk type 2 diabetic patients reduces the amputation rate threefold when compared with more standard care [6].…”
Section: Current Evidence-based Interventionsmentioning
confidence: 99%
“…A recent estimate of the lifetime prevalence of foot ulceration is 15% [6]. It has been demonstrated that a program of intensive weekly multidisciplinary clinic visits with chiropody, education, and use of proper hygiene, hosiery, and protective shoes in high-risk type 2 diabetic patients reduces the amputation rate threefold when compared with more standard care [6]. In this study, high-risk patients were defined as those with foot deformity, or a history of foot ulceration, significant vascular disease, or significant neuropathic disease.…”
Section: Current Evidence-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melville et al 7 found that multidisciplinary interventions such as education to increase patients' knowledge about foot care, podiatry, and therapeutic shoes can improve the condition of the feet and help to reduce ulcer and amputation rates. Various treatments are used for diabetic foot ulcers but the evidence for their eVectiveness is poor.…”
mentioning
confidence: 99%